PENERAPAN TEKNOLOGI DIGITAL DALAM MENINGKATKAN DAYA SAING UMKM DI INDUSTRI KREATIF - Oki Iqbal Khair; Ikram Al Ghifari; Nur Aida El-fitri; Vina Afelia; Lukman Hakim (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
Micro, Small and Medium Enterprises (UMKM) in the creative industry sector play an important role in the Indonesian economy. However, the level of competitiveness of UMKM is still relatively low compared to large businesses, especially in facing global competition and economic digitalization. This research aims to analyze the application of digital technology in increasing the competitiveness of UMKM in the creative industry. The research method used is qualitative with a case study approach on 15 UMKM in the creative industry sector that have implemented digital technology. Data collection techniques were carried out through in-depth interviews, observation and documentation. The research results show that the application of digital technology has a positive impact on increasing the competitiveness of UMKM through several aspects such as expanding market reach through digital platforms, operational efficiency and business management, product and service innovation, and increasing customer engagement. However, there are several challenges faced such as limited human resources, access to capital and technological infrastructure. This research recommends the need for digital mentoring programs, increasing technological literacy, and government policy support to accelerate the digital transformation of creative industry UMKM.